2014
DOI: 10.1242/dev.079129
|View full text |Cite
|
Sign up to set email alerts
|

Cell competition: how to eliminate your neighbours

Abstract: A conventional view of development is that cells cooperate to build an organism. However, based on studies of Drosophila, it has been known for years that viable cells can be eliminated by their neighbours through a process termed cell competition. New studies in mammals have revealed that this process is universal and that many factors and mechanisms are conserved. During cell competition, cells with lower translation rates or those with lower levels of proteins involved in signal transduction, polarity and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
171
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 129 publications
(272 reference statements)
1
171
0
1
Order By: Relevance
“…6B). On the other hand, we cannot exclude the possibility that the higher apoptosis rate could be a result of increased cell competition in the tumor brain (29). The lower apoptosis rate in the tumor brain at 48-96 h ALH might suggest that the tumor cells have evaded apoptosis.…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 90%
See 1 more Smart Citation
“…6B). On the other hand, we cannot exclude the possibility that the higher apoptosis rate could be a result of increased cell competition in the tumor brain (29). The lower apoptosis rate in the tumor brain at 48-96 h ALH might suggest that the tumor cells have evaded apoptosis.…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 90%
“…The lower apoptosis rate in the tumor brain at 48-96 h ALH might suggest that the tumor cells have evaded apoptosis. Alternatively, the lower apoptosis rate could suggest that "vulnerable" cells may have died off because of cell competition (29).…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
“…These results imply that at the early stage of carcinogenesis, normal epithelial cells act as 'immunity' against transformed cells, and we have named this process 'epithelial defense against cancer' (EDAC) . In Drosophila, it has been also shown that normal and transformed epithelial cells often compete with each other for survival, and this phenomenon is called cell competition (Amoyel and Bach, 2014;Baker, 2011;Moreno and Rhiner, 2014). However, detailed molecular mechanisms regulating these non-cell-autonomous processes still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of communication, cell competition is a unique type of short-range communication originally identified in Drosophila. Cells compare their fitness level with those of neighboring cells, and cells with relatively higher fitness become winners, and cells with relatively lower fitness are eliminated as losers (for reviews, see Baker, 2011;Levayer and Moreno, 2013;Vincent et al, 2013;Amoyel and Bach, 2014).…”
Section: Introductionmentioning
confidence: 99%